NEW COMPOSITIONS OF TOOL STEELS FOR COLD AND HOT FORMING AND THEIR HARDENING CAPABILITIES - V. N. Fedulov (Литьë и металлургия)
New compositions of tool steels of increased wear resistance for manufacturing tools of various purposes are considered. The results of this work can be used in the manufacture of cold and hot forming molds and working parts of die casting molds of aluminum and copper alloys, as well as in the manufacture of cutting tools for woodworking and even for plastics molding. In every case you selection of the steels depends on the purpose of use and the required operational life of the tool.